An Empirical Study on “Employees’ Work Behavior”: Pre and Amid Covid-19 Pandemic in Education Sector in Uttarakhand - Dr. Neema Gupta, Ashish K. Gupta, Mr. Samarth Agarwal (International Journal of Advanced Science and Technology, 2020)
In every organization, employees are considered as the most important assets and a valuable resourceof any business. An organization can’t imagine its existence without valuable human resources. Thework behavior of the employees defines the level of success of any organization. The research wasconducted to determine the employees’ working behavior amid covid-19 pandemic during lockdownand comparing it with the working behavior of the employees at the workplace pre covid-19pandemic. Simple random sampling technique and self structured questionnaire were used to collectthe responses from 197 respondents. The derived result was tested against the hypotheses; (i) There isno significant difference between employees’ work behavior in terms of pre and amid covid-19pandemic, (ii) There is a significant difference between employees’ work behavior in terms of pre andamid covid-19 pandemic. The finding showed the rejection of null hypothesis and acceptance of thealternate hypothesis. In order to check the significant difference between employees’ work behavior interms of pre and amid covid-19 pandemic, SPSS was used to analyze the surveyed data. To test thehypotheses Reliability test and independent t-test technique were taken.